A combined numerical and experimental approach to study the carbonization of low-rank coal ellipsoidal briquettes. (31st August 2019) - Zhuo, Yuting; Li, Changxing; Wu, Chenglin; Shen, Yansong
Highlights: A combined numerical and experimental approach is developed to study carbonization process. The approach integrates experiments, a DEM model and a CFD model. The approach is applied to low-rank coal ellipsoidal briquettes in a pilot-scale coke oven. Effects of briquettes packing structure on carbonization are identified. Increased particle dropping height and vibration lead to denser packing structure and higher carbonization efficiency. Abstract: This paper reports a combined numerical and experimental approach to study the coal carbonization process. It is applied to low rank coal ellipsoidal briquettes carbonization in a pilot-scale coke oven for demonstration. The integrated mathematical model integrates a DEM model to simulate the packing process of ellipsoidal briquettes in the oven and a CFD model to simulate the flow and thermochemical behaviours related to the carbonization process. The model is validated against the experimental measurements in the pilot-scale coke oven. The comprehensive in-furnace phenomena in the carbonization process are simulated, in terms of flow, temperature, gas composition, and carbonization characteristics. The simulation results indicate that it is necessary to include the briquettes packing structure evolution in the carbonization modelling for reliably describing the in-furnace phenomena. Then the effects of some briquette packing parameters, including briquette dropping height and vertical vibration, on the evolutions of packing structure and carbonization behaviour are studied. It is indicated that the dense packing structure resulting from higher dropping height and one-dimensional vertical vibration before the carbonization can improve the heat and mass transfers between the gas and bed, and thus can improve the carbonization efficiency. The computational cost of this approach as well as its future application are discussed. This model provides a cost-effective tool for understanding and optimizing the carbonization process of non-spherical low rank coal briquettes.